DETERMINAN MINAT MUZAKKI MEMBAYAR ZAKAT PADA BAZNAS DI KABUPATEN MANDAILING NATAL - Nur Saidah; Iqlima Azhar; Tuti Meutia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study aims to determine the factors that influence the interest of muzakki to pay zakat at Baznas in Mandailing Natal Regency. The population of this study are muslims who have met the requirements to pay zakat in Mandailing Natal. The method of determining the sample using the slovin formula. The sampling technique used stratified random sampling. Data collection was carried out by distributing questionnaires to 143 respondents. The data obtained were then analyzed using SPSS(Statistical Package fot the Sosial Sciensce). This research method shows that trust has no positive and significant effect on muzakki’s intention to pay zakat, transparency has a positive an significant effect on muzakki’s intention to pay zakat and the level of religiosity has a positive and significant effect on muzakki’s interest in paying zakat at Baznas in Mandailing Natal District. Based on this study there are still relatively small and only amounting to 143 respondents and does not cover all Mandailing Natal District. Then for further reseatchers it is suggested to expand the scope of research and add several variables such as income level and education level in paying zakat